Generation and management of fats, oil and grease in food waste among residents in Precinct 14, Putrajaya, Malaysia - Che Wil, Lili Mastura (2018)
Fats, Oil and Grease (FOG) is a result of cooking and can always be found in daily domestic food waste. The improper management of domestic FOG waste causes many environmental problems as a result of pipe blockage and sewage overflow. Thus this study focused on gaining knowledge on the management of domestic FOG waste among the households in the residential area of Precinct 14, Putrajaya. This study had been structured with three objectives. The first objective of this study was to assess the level of awareness, attitude and practices towards domestic FOG waste among households in Precinct 14, Putrajaya. The first objective was achieved using the questionnaire survey method. A total of 453 respondents from Precinct 14, Putrajaya were involved in the survey. The result showed that households in Precinct 14, Putrajaya have a high level of awareness and attitude but a modest level of practice towards domestic FOG waste management. The second objective of this study was to determine the generation rate and composition of FOG waste from food waste of households in Precinct 14, Putrajaya. There were seven households involved in this second objective, where lab analysis with the involvement of Soxhlet Extraction Method was used to obtain the results. The result of the analysis showed that the total collected food waste was 18.983kg over a period of seven days. The range of FOG composition in every gram of food waste generated per household in Precinct 14, Putrajaya was found to be between 4.80% and 38.60%. The total FOG generation for seven selected households in seven days was approximately 0.955kg. The third objective of this study was to identify the factors contributing towards domestic FOG waste generation. A linear regression analysis was used to achieve this third objective. The results from the linear regression analysis revealed that the factors influencing the FOG waste generation were attitude, practice, age, level of education and the number of family members. This study had managed to reveal the actual composition of FOG waste in the daily food waste generated by the households in Precinct 14, Putrajaya.The rate of FOG composition and generation can be controlled with a better attitude and practice on food waste management. Practicing proper food waste management is also able to improve the quality of the environment. Proper management practices of FOG waste can be instilled through good environmental education.